SELNET clinical practice guidelines for bone sarcoma. (June 2022) - Blay, JY; Palmerini, E.; Bollard, J.; Aguiar, S.; Angel, M.; Araya, B.; Badilla, R.; Bernabeu, D.; Campos, F.; CHS, Caro-Sánchez; Carvajal Montoya, A.; Casavilca-Zambrano, S.; et al.
Abstract: Bone sarcoma are infrequent diseases, representing < 0.2% of all adult neoplasms. A multidisciplinary management within reference centers for sarcoma, with discussion of the diagnostic and therapeutic strategies within an expert multidisciplinary tumour board, is essential for these patients, given its heterogeneity and low frequency. This approach leads to an improvement in patient's outcome, as demonstrated in several studies. The Sarcoma European Latin-American Network (SELNET), aims to improve clinical outcome in sarcoma care, with a special focus in Latin-American countries. These Clinical Practice Guidelines (CPG) have been developed and agreed by a multidisciplinary expert group (including medical and radiation oncologist, surgical oncologist, orthopaedic surgeons, radiologist, pathologist, molecular biologist and representatives of patients advocacy groups) of the SELNET consortium, and are conceived to provide the standard approach to diagnosis, treatment and follow-up of bone sarcoma patients in the Latin-American context. Highlights: Bone sarcoma (STS) encompass more than 30 different histologic subtypes. Clinical practice guidelines for bone sarcoma still lack in Latin-American countries. Tailored clinical guidelines are instrumental to improve outcome in bone sarcoma patients in Latin-American countries. This is the first review establishing bone sarcoma guidelines for the purpose of Latin-American clinical practices to our knowledge.